Continuance Use Intention in the use of E-wallets by using the Expectation Confirmation Model through E-Satisfaction - Khoirul Umam, Muhamad; Puspawati, Dewita (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to test the use of e-wallets against continuance use intention by using expectation confirmation. This research Model uses a type of quantitative approach with the method of explanation (explanatory research). The population in this study is an e-wallet application users in Surakarta , this study uses non probability sampling method and to determine the sample using convinence sampling technique, obtained a sample of 100 respondents. The method of data analysis in this study used the technique of Structural Equation Modeling-Partial Least Square (SEM PLS). The test results showed that confirmation, and and perceived sequence had no effect on the continuity of use intention; perceived usefulness and satisfaction had no effect on the continuity of use intention, confirmation, and perceived usefulness had no effect on satisfaction; perceived sequence affects satisfaction, while satisfaction variable is stated to be able to mediate the relationship of perceived usefulness to continuance use intention mediated by satisfaction. While the relationship of confirmation variables, and perceived sequence to continuance use intention is not able to be mediated by satisfaction variables